Extracurricular Activity Intensity and Adolescent Risk-Taking: Exploring Interactive Effects of Contextual Risk and Coping Efficacy. (17th March 2017) - Heaslip, Gabriel P.; Barber, Bonnie L.
Abstract : Adolescence is a period of heightened risk-taking. Therefore it is important to investigate positive settings that can facilitate healthy adolescent development and reduce risk-taking behaviour. This study investigated the relations between non-sporting extracurricular activity participation intensity and risky behaviour. Adolescents' coping efficacy was tested as a moderator between extracurricular activity participation and risk-taking among adolescents at different levels of contextual risk. Adolescents ( N = 1, 599) across Western Australia were surveyed. Results for moderately at-risk youth indicated a significant interaction, such that greater activity intensity was associated with less risk-taking for adolescents with higher coping efficacy. However, higher intensity activity participation predicted more risk-taking for adolescents with low coping efficacy.